Lourenço Filho e a coleção Biblioteca de Educação : uma análise dos prefácios escritos por esse educador - Oliveira, Priscila Marília de (Universidade Federal de São Carlos, 2015)
This thesis aims to reveal and to analyze which design New Lourenço Filho School brought up through the prefaces which were published in works Collection Education Library. The assumptions of this research focus in the field of history of pedagogical ideas and historical theory - Critical (Saviani, 2007) adding to these discussions contributions of Certeau (2008). The results point to the conclusion that the design of the New School created and propagated by Lourenço Filho in prefaces written by him - which were published in works Collection Education Library - although fragmented and heterogeneous, was designed with a homogenizer character. By advocating a reform speech, Lourenço Filho created an imaginary in which he articulated by this movement was a departure from what until then had been perpetrated in the educational field. Thus, this new school of design was intended, through the works Collection Education Library, mold/direct the mentality of the teachers of the time.
Keywords: Coleção Biblioteca de Educação; Lourenço Filho; Concepção de Escola Nova; Education Library Collection; Lourenço Filho; New School's conception; CIENCIAS HUMANAS::EDUCACAO